COLLABORATIVE GOVERNANCE DALAM UPAYA PERCEPATAN PENURUNAN STUNTING MELALUI PROGRAM DAYCARE RUMAH PELITA DI KECAMATAN SEMARANG UTARA TAHUN 2024 - Bintang Ayu Santika; Dewi Erowati (Journal of Politic and Government Studies, 2026)
Stunting cases in North Semarang District still show a high number compared to other areas in Semarang City, despite various management efforts. This condition indicates that sectoral interventions have not been able to produce optimal results, so a collaborative approach involving various actors is needed. The government then introduced the Rumah Pelita Daycare Program as a form of Collaborative Governance implementation in an effort to accelerate stunting reduction. This study aims to analyze the collaboration process between actors and the obstacles faced in program implementation. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation, involving the Health Office, Bandarharjo Community Health Center, nutritionists, HIMPSI Central Java, and the community. The results of the study indicate that the Collaborative Governance process in the implementation of the Rumah Pelita Daycare Program in North Semarang District is running quite well, marked by collaborative actions between actors that cannot be carried out independently. This collaboration is reflected in the implementation of health checks involving non-governmental organizations and community participation in parenting classes. Furthermore, program implementation is carried out systematically through a clear and sustainable workflow, starting from the planning stage, program implementation, and evaluation. This program also has an impact in the form of a reduction in stunting rates. However, challenges include limited human resources, low community participation, and the absence of private sector involvement, resulting in limited collaboration. This study recommends improving human resource capacity, expanding private sector involvement, and strengthening community participation to enhance program effectiveness and sustainability.